An ICT-Driven Hybrid Automation System for Elderly Care Support: A Rehabilitation Facility Study Case. Issue 1 (2nd January 2016) - Evchina, Yulia; Martinez Lastra, Jose Luis
Abstract: The demographic statistics in developed countries suggest growth in the elderly segment of the population. At the same time, other studies forecast a shortage of nurses, increasing the pressure on hospitals to provide treatment for longer periods of time. These trends suggest a need for new ways of taking care of the elderly population that support safe, comfortable, and independent living. Meanwhile, prominent advances in information and communications technology (ICT) have enabled new systems that address various needs of the elderly. This article presents a case study of a rehabilitation facility located in Tampere, Finland, that uses an automation system in which ambient assisted living (AAL) and building automation (BA) system functionalities are combined. It details a field study summarizing the needs of the users, describes functional scenarios supported by the system, and reports the results of the first usability tests suggesting acceptance of a new technology by residents and caregivers. The unique combination of ambient assisted living and building automation offers a safer and more comfortable environment for the elderly as well as helps caregivers on-site in managing their workloads.